(untitled) (Research, Society and Development, 2025)
The study conducted in the Pont-Tamarin region, Zone I (Haiti), aims to diagnose local agricultural systems and identify and assess the parameters influencing their sustainability. Using an exploratory methodology that included questionnaires administered to 42 farmers and field visits. The results reveal a predominance of diverse crops such as leeks, carrots, rice, corn, sorghum, beans, beets, eggplants, peppers, and tomatoes, alongside limited livestock farming by a minority. Although some farmers adopt organic or transitional practices, the majority rely on conventional agriculture for economics purpose and to meet the market demands, thereby compromising the sustainability of agroecosystems in the study area. Despite being aware of the challenges, farmers struggle to change their practices without external support. The study concludes that improving agricultural sustainability in the region depends on technical assistance and training from public authorities to promote agroecological practices and ensure a transition toward more resilient and environmentally respectful farming.